Thyroid Function in 509 Premature Newborns Below 31 Weeks of Gestational Age: Evaluation and Follow-up - Ariadna Campos-Martorell; Alicia Montaner Ramon; Karla Narváez Barros; José Luis Marin Soria; Rosa Maria López Galera; Diego Yeste Fernández; María Clemente León (Galenos Yayincilik, 2022)
INTRODUCTION: Preterm and low birth weight (LBW) neonates may present with thyroid dysfunction during a critical period for neurodevelopment. These alterations can be missed on routine congenital hypothyroidism (CH) screening which only measures thyroid stimulating hormone (TSH). The objective of this study was to evaluate a protocol for thyroid function screening (TFS) six years after national implementation. METHODS: Serum TSH and free thyroxine (fT4) were measured during the second week of life in neonates below 31 weeks. Patients with abnormal TFS (fT4 <0.8 ng/dL and/or TSH >5 mU/L) were followed up with repeated tests until normal levels were reported. Patients who were still on levothyroxine (LT4) at three years of age were re-evaluated. RESULTS: Five-hundred and nine neonates were included. Thyroid dysfunction was detected in 170 neonates (33%); CH n=20 (3.9%) including typical CH n=1; delayed TSH elevation CH n=19; hypothyroxinemia of prematurity (HOP) n=15 (2.9%); and transient hyperthyrotropinemia n=135 (26.5%). Twenty-one neonates (4.1%) were treated (20 for CH and 1 for HOP). At 3-year follow-up only three patients were diagnosed with permanent CH and still need treatment. LBW infants tended to have TSH levels higher than those with adequate weight. DISCUSSION AND CONCLUSION: This protocol was able to detect thyroid dysfunction in preterm neonates who were not identified by the current program based on TSH determination in whole-blood. This thyroid dysfunction seems to resolve spontaneously in a few months in the great majority of neonates, but in some cases LT4 could be needed. There is a critical need for specific guidelines regarding the follow-up and re-evaluation of transient CH in preterm neonates.